When Have All the Graduates Gone? Internal Cross-State Migration of Graduates in Germany 1984-2004 - Oliver Busch (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The present paper analyzes the out-migration of graduates to other German states or abroad based on the German Socio-Economic Panel (GSOEP). Applying duration analysis, it can be shown that, ten years after graduation, slightly more than seventy percent of the graduates still live in the state where they completed their studies. The parametric estimation model identifies personal characteristics that are highly correlated with out-migration and permanent residence respectively. The analysis confirms previous results that nonresident students exhibit a significantly higher emigration propensity than resident fellows.
Keywords: H52; I2; J61; R23; 330; Brain drain; nonresident students; fiscal externalities; duration analysis; GSOEP